The inhibitory effect of thiosulfinate on volatile fatty acid and hydrogen production from anaerobic co-fermentation of food waste and waste activated sludge. (February 2020) - Tao, Ziletao; Yang, Qi; Yao, Fubing; Huang, Xiaoding; Wu, You; Du, Mingting; Chen, Shengjie; Liu, Xuran; Li, Xiaoming; Wang, Dongbo
Graphical abstract: Highlights: Thiosulfinate reduced hydrogen yield from anaerobic co-fermentation of WAS and FW. Thiosulfinate induced VFA metabolic pathway into propionic acid type. Thiosulfinate inhibited the relative activities of functional enzymes. Thiosulfinate damaged the cell membrane structure of anaerobic microbes. Abstract: Thiosulfinate, a nature antibiotic, existed in all parts of Allium thereby accumulating in kitchen waste vastly. However, few literatures were available related to its influence on volatile fatty acids (VFA) and hydrogen production when kitchen waste digestion technology was applied. This study aimed to explore the inhibitory effect and the relevant mechanism. Experimental results showed that the hydrogen accumulation decreased from 23.2 ± 0.8 to 8.2 ± 0.1 mL/g VSS (volatile suspended solid) and maximal total VFA yield decreased from 765.7 ± 21.2 to 376.4 ± 21.7 mg COD (chemical oxygen demand)/g VSS when the dosage of thiosulfinate increased from 0 to 12.5 µg/g VSS. The mechanism study indicated, compared with control group, that the butyric acid decreased from 59% to 20.1% of total VFA yield when reactor in present of 12.5 µg/g VSS thiosulfinate. Moreover, the relative activities of functional enzymes were inhibited 73.4% (butyryl-CoA) and 72.7% (NADH), respectively.